Design and Build Payment Gateways in Sharia-Based E-Commerce (Case Study: Murabahah Ijabqabul.Id Contract) - Mohammad Izzi Fajrin; Irwan Alnarus Kautsar; Sukma Aji (Procedia of Engineering and Life Science, 2022)
As technology is increasingly advanced and developing, shopping that was originally done in supermarkets is now done online. The COVID pandemic has also made people switch to shopping online, as in e-commerce. Research also shows that e-commerce in Indonesia has increased by 5–10 times during the pandemic. Ecommerce has always been associated with simple and convenient purchasing and payment methods. Ijabqabul.id is an e- commerce platform that provides a variety of product categories. In order to improve services for the development of ijabqabul.id e-commerce, particularly in terms of payment transactions, a payment gateway system as an online payment system is required. This research will result in a web service-based payment gateway system with JSON output. A payment gateway system is built using the Python programming language and the Flask framework. The Postman application is used to test a payment gateway system that is based on web services. Agile Development is the method used in the development of the payment gateway system. This method is carried out through brainstorming with researchers from the sharia study program. The developed payment gateway system generates a virtual account number, making the transaction process simpler, safer, and more convenient